Improving Students' Cognitive and Psychomotor Performance through the Development of Project-Based Clinical Chemistry Learning Modules - Ratih Dyah Puspitasari; Nelson Nelson; Indra Lasmana Tarigan (Hydrogen: Jurnal Kependidikan Kimia, 2023)
The present study aimed to enhance students' cognitive and psychomotor performance through the implementation of a project-based learning module in clinical chemistry. The module was developed using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model and was tailored to address real-life clinical problems, possessing characteristics of self-instructional, self-contained, stand-alone, adaptive, and user-friendly. Validation by media and subject matter experts revealed a strong eligibility of the module with a media expert assessment score of 87.7% and a subject matter expert score of 90.4%. The students' response, as measured using the Likert scale, indicated a "Very Good" rating with a score of 92.85%. The results showed a significant improvement in both cognitive and psychomotor performance, with increases of 14.24% and 24.78%, respectively.